Defining the technical skills of teamwork in surgery. - Healey, A; Undre, S; Vincent, C (2006)
Developments in surgical technology and procedure have accelerated and altered the work carried out in the operating theatre/room, but team modelling and training have not co-evolved. Evidence suggests that team structure and role allocation are sometimes unclear and contentious, and coordination and communication are not fully effective. To improve teamwork, clinicians need models that specify team resources, structure, process and tasks. They also need measures to assess performance and methods to train teamwork strategically. An effective training strategy might be to incorporate teamwork with other technical skills training in simulation. However, the measures employed for enhancing teamwork in training and practice will need to vary in their object of analysis, level of technical specificity, and system scope.